Optimised In2S3 Thin Films Deposited by Spray Pyrolysis - Hristina Spasevska; Catherine C. Kitts; Cosimo Ancora; Giampiero Ruani (International Journal of Photoenergy)
Indium sulphide has been extensively investigated as a component for different kind of photovoltaic devices (organic-inorganic hybrid devices, all inorganic, dye sensitized cells). In this paper, we have optimised the growth conditions of indium sulphide thin films by means of a low cost, versatile deposition technique, like spray pyrolysis. The quality of the deposited films has been characterised by micro-Raman, vis-UV spectroscopy, and atomic force microscopy. Substrate deposition temperature and different postdeposition annealing conditions have been investigated in order to obtain information about the quality of the obtained compound (which crystalline or amorphous phases are present) and the morphology of the deposited films. We have shown that the deposition temperature influences strongly the amount of amorphous phase and the roughness of the indium sulphide films. Optimised postdeposition annealing treatments can strongly improve the final amount of the beta phase almost independently from the percentage of the amorphous phase present in the as deposited films.